(untitled) (Indian Journal of Child Health, 2019)
Infantile tremor syndrome (ITS) is usually present in purely breastfed babies of vegetarian mothers with acute regression of developmental milestones, pallor with megaloblastic anemia, bleating goat like cry, knuckle, and other body site hyperpigmentation, apathy, listlessness, and brown scanty hair. This is usually due to Vitamin B12 deficiency and symptoms can be reversed with Vitamin B12 supplementation. There are only a few anecdotal case reports of seizure in children with ITS. Hereby, we are presenting a case of a child having epileptic spasms associated with ITS along with megaloblastic anemia with hypersegmented neutrophils in peripheral smear and high mean corpuscular volume. The child was successfully treated with Vitamin B12 supplementation and oral corticosteroids. This case report underscores the importance of considering the possibility of Vitamin B12 deficiency in any child presenting with megaloblastic anemia with either generalized tremulousness with or without seizures.